Agricultural Machinery Socialization Service Adoption, Risks, and Relative Poverty of Farmers - Hailan Qiu; Mingrui Feng; Yiming Chi; Mingzhong Luo (Agriculture, 2023)
Agricultural machinery socialization services are an important means of alleviating poverty and promoting agricultural modernization. Based on 2750 items of survey data from farmers in Henan Province, this paper empirically tests the impact and mechanism of agricultural machinery socialization service adoption on the relative poverty of farmers by using a binary logit model and mediation effect model. The results show that the adoption of agricultural machinery socialization services has a significant negative impact on the relative poverty of farmers. The reduction in natural risk plays an intermediary role in the impact of the adoption of agricultural machinery socialization services on the relative poverty of farmers. The size of the household labor force and the land operation scale affect the poverty reduction effect of agricultural machinery socialization services. It can be seen that in the relative poverty governance stage, we should improve the development of the agricultural machinery socialization service system, enhance the risk resistance of farmers, build a supporting system for farmers’ employment skills training, and encourage an orderly connection between the large-scale operation of agricultural land and the large-scale operation of services so as to fully realize the poverty reduction role of agricultural machinery socialization services.